PERTANGGUNGJAWABAN MAKELAR DAN KOMISIONER KEPADA PIHAK KETIGA BERDASARKAN HUKUM DAGANG INDONESIA - Ayu Putri Rainah Petung Banjaransari (Jurnal Yustisiabel, 2021)
Brokers and Commissioners as intermediary traders have significant differences in terms of obligations to third parties, apart from having similarities in terms of objectives. Each of these intermediate traders has their own responsibilities and rules in carrying out their duties and obligations for goods or services that are defective and legally unsafe. This study aims to specifically discuss and analyze the two jobs as intermediary traders in the realm of legal science because errors often occur. This study uses a normative method with descriptive and qualitative approaches based on existing literature sources and research data. After going through discussion, analysis, and comparison, findings were obtained about the similarities between brokers and commissioners in terms of their objectives and essence. Apart from that, it was also found that there were differences in accountability between brokers and commissioners, which resulted in different impacts on an engagement.